Exploration of the Effect of Electroencephalograph Levels in Experienced Archers. (July 2014) - Twigg, Peter; Sigurnjak, Stephen; Southall, Dave; Shenfield, Alex
This preliminary study aims to record the brainwaves of two experienced archers, while undertaking the process of aiming and shooting arrows at a target. The brainwaves are then analysed for repeatability and dominant characteristics within individual electroencephalograph activity. Images of the archers are also recorded to establish reference points within the shot cycle for correlating the electroencephalograph data sets.